Targeting miR‐126 disrupts maintenance of myelodysplastic syndrome stem and progenitor cells. Issue 10 (14th October 2021) - Wang, Huafeng; Sun, Jie; Zhang, Bin; Zhao, Dandan; Tong, Hongyan; Wu, Herman; Li, Xia; Luo, Yingwan; Dong, Dan; Yao, Yiyi; McDonald, Tinisha; Stein, Anthony S.; et al.
Abstract: Background: Myelodysplastic syndrome (MDS) arises from a rare population of aberrant hematopoietic stem and progenitor cells (HSPCs). These cells are relatively quiescent and therefore treatment resistant. Understanding mechanisms underlying their maintenance is critical for effective MDS treatment. Methods: We evaluated microRNA‐126 (miR‐126) levels in MDS patients' sample and in a NUP98‐HOXD13 (NHD13) murine MDS model along with their normal controls and defined its role in MDS HSPCs' maintenance by inhibiting miR‐126 expression in vitro and in vivo. Identification of miR‐126 effectors was conducted using biotinylated miR‐126 pulldown coupled with transcriptome analysis. We also tested the therapeutic activity of our anti‐miR‐126 oligodeoxynucleotide (miRisten) in human MDS xenografts and murine MDS models. Results: miR‐126 levels were higher in bone marrow mononuclear cells from MDS patients and NHD13 mice relative to their respective normal controls ( P  < 0.001). Genetic deletion of miR‐126 in NHD13 mice decreased quiescence and self‐renewal capacity of MDS HSPCs, and alleviated MDS symptoms of NHD13 mice. Ex vivo exposure to miRisten increased cell cycling, reduced colony‐forming capacity, and enhanced apoptosis in human MDS HSPCs, but spared normal human HSPCs. In vivo miRisten administration partially reversed pancytopenia in NHD13 mice and blocked the leukemic transformation (combination group vs DAC group, P < 0.0001). Mechanistically, we identified the non‐coding RNA PTTG3P as a novel miR‐126 target. Lower PTTG3P levels were associated with a shorter overall survival in MDS patients. Conclusions: MiR‐126 plays crucial roles in MDS HSPC maintenance. Therapeutic targeting of miR‐126 is a potentially novel approach in MDS. Abstract : MiR‐126 levels are higher in stem/progenitor cells from MDS patients relative to normal counterparts. MiR‐126 KO inhibits MDS stem/progenitor cell maintenance. In vivo administration of a miR‐126 inhibitor in combination with decitabine partially reverses pancytopenia in a murine MDS model and decreases the risk of leukemic transformation. The non‐coding RNA PTTG3P is a downstream target of miR‐126 in MDS cells.